Blood monocyte counts as a potential prognostic marker for idiopathic pulmonary fibrosis: analysis from the Australian IPF registry. Issue 4 (2nd April 2020) - Teoh, Alan K.Y.; Jo, Helen E.; Chambers, Daniel C.; Symons, Karen; Walters, Eugene H.; Goh, Nicole S.; Glaspole, Ian; Cooper, Wendy; Reynolds, Paul; Moodley, Yuben; Corte, Tamera J.
Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive, fibrosing lung disease that leads to unrelenting dyspnoea and chronic cough, and ultimately respiratory failure [1]. IPF is characterised by a variable disease course that remains difficult to predict for an individual at diagnosis [2]. In the current era, with the advent of anti-fibrotic therapy which can slow disease progression, it is increasingly important to identify patients with early disease and to target those patients who are at most risk of rapid decline [3]. However, despite multiple studies proposing novel potential prognostic biomarkers, the current American Thoracic Society/European Respiratory Society/Japanese Respiratory Society/Latin American Thoracic Society guideline statements dismissed the use of these biomarkers except in a research capacity [3, 4]. Blood monocytes have been recently proposed as a potential prognostic marker for IPF. Data from the Australian IPF registry have shown that elevated monocytes, neutrophils and total leukocytes significantly predict poorer survival in IPF patients. http://bit.ly/38GP7f0